2012
DOI: 10.1016/j.diii.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Breast inflammation: Indications for MRI and PET-CT

Abstract: Breast MRI should not be used for differential diagnosis between inflammatory breast cancer and acute mastitis (AM) prior to treatment. When mastitis symptoms persist after 10 to 15 days of well-managed medical treatment, MRI may be performed in addition to an ultrasound examination, a mammogram and to taking histological samples, in order to eliminate inflammatory breast cancer (IBC). For staging, MRI would seem to be useful in looking for a contralateral lesion, PET-CT for finding information about remote me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 33 publications
0
7
0
2
Order By: Relevance
“…In addition, GM may not be readily differentiated from breast cancer radiologically (1-18). It generally involves one breast, although bilateral involvement has also been reported (2, 5, 7, 10).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GM may not be readily differentiated from breast cancer radiologically (1-18). It generally involves one breast, although bilateral involvement has also been reported (2, 5, 7, 10).…”
Section: Discussionmentioning
confidence: 99%
“…Rieber et al [ 18 ] found that MRI did not provide any additional information that was critical in differentiating idiopathic granulomatous mastitis from inflammatory carcinoma, since both exhibit signs of inflammation. In a study by de Bazelaire et al [ 19 ], dynamic contrast MR imaging did not prove to be really discriminatory either, as intense early enhancement (>100 % before 90 s) was found in the majority of cases of inflammatory breast carcinoma and almost half of the patients with mastitis, the enhancement kinetics of both conditions being analogous produced by vascular endothelial growth factor (VEGF). At best, MRI may play a complementary role to increase conspicuity of lesions that are not visualised by mammograms and ultrasound adequately.…”
Section: Role Of Mrimentioning
confidence: 99%
“…PET/CT may give false-negative results in cases of small lesions, particularly in the liver and lung parenchyma. Also, falsepositive results may occur in cases of inflammation or infection (5). Ipsilateral axillary lymph node uptake due to extravasation or partial subcutaneous injection of the antecubital region has been reported, thus giving false-positive results in some cases.…”
Section: Discussionmentioning
confidence: 94%